2021
DOI: 10.3389/feduc.2021.687661
|View full text |Cite
|
Sign up to set email alerts
|

Formative Assessment of Social-Emotional Skills Using Rubrics: A Review of Knowns and Unknowns

Abstract: Educational practitioners have been increasingly interested in the use of formative assessment and rubrics to develop social-emotional skills in children and adolescents. Although social-emotional rubrics are nowadays commonly used, a thorough evaluation of their psychometric properties has not been conducted. In this scoping review, we examine the knowns and unknowns of the use of formative assessment approaches and rubrics in social-emotional learning. We first review initiatives of formative assessment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Although current research praises the bene ts this combination may bring, there may be a risk of inhibiting divergent thinking when learners overanalyze exemplars instead of re ecting on their own experiences (Panadero et al, 2022;. Furthermore, the rubric has three quality levels in contrast to the recommended four to six levels, even though this is not exceptional for multidimensional constructs (Pancorbo et al, 2021;Nkhoma et al, 2020;Jönsson and Panadero, 2017). Nonetheless, both aspects warrant more research but also emphasize the importance of adequately training learners in using rubrics and exemplars.…”
Section: Limitationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although current research praises the bene ts this combination may bring, there may be a risk of inhibiting divergent thinking when learners overanalyze exemplars instead of re ecting on their own experiences (Panadero et al, 2022;. Furthermore, the rubric has three quality levels in contrast to the recommended four to six levels, even though this is not exceptional for multidimensional constructs (Pancorbo et al, 2021;Nkhoma et al, 2020;Jönsson and Panadero, 2017). Nonetheless, both aspects warrant more research but also emphasize the importance of adequately training learners in using rubrics and exemplars.…”
Section: Limitationsmentioning
confidence: 95%
“…Nonetheless, the 'measurement paradigm' still dominates health profession education through an emphasis on assessment of learning (AoL), which follows an objectivist and summative approach by psychometrically assessing learning outcomes (Peeters and Sexton, 2020;Nieminen et al, 2023). Correspondingly, assessment practices have mostly focused on the outcomes of learning for which knowledge and skills are typically assessed by means of a test or nal project (Hayes et al, 2018;Pancorbo et al, 2021). In contrast, the emergence of the 'postpsychometric' phase of assessment is associated with a growing awareness and accountability of faculty in providing transparency in assessment and in using tools to gather information about learners' progression to scaffold learning and re ection (Nishizuka, 2022;Panadero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this tool may help the individual teacher to identify strengths and developmental needs, but also provide feedback on how to increase one's SEMS mastery. Due to various assessment challenges (Duckworth and Yeager, 2015;Greiff and Kyllonen, 2016;Abrahams et al, 2019), such a tool will preferably use a 360-degree multi-informant approach including self-ratings and multiple observer-ratings (e.g., students, supervisors, directors, see Pancorbo and De Fruyt, 2021). Additionally, due to their sensitivity for response styles, such as acquiescence (Primi et al, 2021), faking, and bandwidth-fidelity problems (Cronbach and Gleser, 1965) additional methods of assessment, beyond the traditional self-report questionnaires using Likert ratings, should be considered (see Abrahams et al, 2019, for more detail), such as for example situational judgment formats.…”
Section: Next Stepsmentioning
confidence: 99%
“…Students' overall mean of the post-test scores on the relationship skills after using the activity package was statistically significantly higher than pre-test at the .05 level of significance and when considered separately by the components of relationship skills, it was found that all of them were higher mean at the .05 level of significance, except the components of teamwork that was higher mean but not significance. (Anderson, 2013;Crosby, 2011;Pancorbo Valdivia et al, 2021)…”
mentioning
confidence: 99%